Planning for a Sustainable Cultural Heritage Sector in a New Age. Issue 1 (23rd September 2021) - Prince, David; Laven, Daniel; Lawson, Steven
This paper was prepared as part of the special collection on COVID-19 and the museum. The authors discuss the risks and uncertainties that the pandemic has introduced into the master planning process for cultural sites and resources. The paper concludes with reflections on how the heritage and cultural sector can best cope with these new realities.